Vitamin E supplementation can alleviate negative effects of heat stress on egg production, egg quality, digestibility of nutrients and egg yolk mineral concentrations of Japanese quails - Şahin, Kazım; Şahin, Nurhan; Onderci, M (Elsevier Sci Ltd, 2002)
The aim of this study was to determine if the negative effects of high ambient temperature (34 degreesC) on egg production, egg quality, digestibility of nutrients, and mineral content of egg yolk could be alleviated by dietary vitamin E (dl-alpha-tocopheryl acetate) supplementation in laying Japanese quails (Coturnix coturnix japanica). Japanese quails (n = 240; 7-week-old) were divided into eight groups, 30 birds per group. The quails were fed either a basal diet or the basal diet supplemented with either 125, 250 or 500mg of dl-alpha-tocopheryl acetate/kg of diet. Birds were kept at 22degreesC and 55% relative humidity (RH). At 14 weeks of age, the thermo-neutral (TN) group remained in the same temperature as at the beginning of the experiment, whereas the heat stress (HS) group was kept at an environment-controlled room at 34degreesC and 44% RH for 3 weeks. Heat exposure decreased performance when basal diet was fed (P = 0.001). With 250 and 500 mg/kg of diet, an increase in body weight (P = 0.01), feed intake (P = 0.01), egg production (P = 0.001), and improvement in feed efficiency (P = 0.01) was found with vitamin E supplementation in quails reared under heat stress conditions (HS). Similarly, egg weight (P = 0.01), egg specific gravity (P = 0.01), egg shell thickness (P = 0.05) and Haugh unit (P = 0.01) were positively influenced by vitamin E supplementation. Heat exposure decreased digestibility of dry matter (DM) (P = 0.03), organic matter (OM) (P = 0.05), crude protein (CP) (P = 0.02), ether extract (EE) (P = 0.05) and were elevated by supplemental vitamin E (P less than or equal to 0.02). Egg yolk concentrations of Zn, Fe, and Mn decreased under high environmental temperature and were increased to values of the control group (P = 0.001) when dietary vitamin E was supplemented. No significant differences in any values were observed in TN groups. Results of the present study conclude that supplementation with 250 mg alpha-tocopherol acetate/kg of diet can be considered to be protective management practice in a quail diet, reducing the negative effects of heat stress. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Carcass Characteristics; Laying Hens; Performance; Temperature; Digestion; Chickens; Feed